Buddhism of Nepalmandala: Scope and Challenges in Modern Context - Shakya, Manik Ratna (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: Buddhism of Nepalmandala is also known as Newar Buddhism. This Buddhism has carried a long history of Nepal; it can demonstrate Nepalese art and architecture, and it has been followed by the indigenous people of Nepal for a long time. The sacred Buddhist monuments of this Buddhism, such as Swayambhu and Bauddha Stupa are listed in the world heritage. This Buddhism is preserving the ancient tradition of Nalanda and Bikramsila University which were world-renowned Buddhist universities in the world in the ancient period around 7-9 centuries. Objective: This paper is meant to highlight the historicity and essential features of Buddhism of Nepalmandala as well as its challenges at present situation. Besides, in this paper, an attempt is made to address the cause of major challenges and its solution. Methodology: Library-based research methodology has been used in this paper which involves historical and textual analysis to examine the historical tradition of Buddhism of Nepal Mandala. Result: As recorded in history, renowned Buddhist masters of Buddhism of Nepalmandala named Silamanju, Kalyanmitra had established Buddhist lineage in Tibet. They had played an essential role in propagating Buddhist philosophy, logic, doctrine, contemplation etc in Tobet. Till now, there are 300 Buddhist monasteries of the Buddhism only in the Kathmandu valley, kingdom of Nepal. However, due to the different types of obstacles, this Buddhism is facing various types of challenges at present. Conclusion: Most of the Buddhist monasteries are in critical condition because of the influence of modern construction. The number of followers and practitioners of this Buddhism is being minimized and the young generation are being far from the education of this Buddhism because of the influence of modernity.